NiCo2O4-Nanoparticle-Catalyzed Microwave-Assisted Dehydrogenative Direct Oxidation of Primary Alcohols to Carboxylic Acids under Oxidant-Free Conditions - Anchal, Kumari; Patel, Ashok R.; Banerjee, Subhash (Synlett, 2024)
Here, we report the NiCo2O4-nanoparticle-catalyzed dehydrogenative direct oxidation of primary alcohols to carboxylic acid in the presence of KOH under microwave irradiation in the absence of any oxidant in good to excellent yields (75–99%) within a short reaction time (5–10 min). The polycrystalline cubic spinel phase of NiCo2O4 nanoparticles (NPs) with an average size of 25 nm were synthesized by the co-precipitation method and analyzed properly by using powder X-ray diffraction, field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and transmission electron microscopy measurements. The NiCo2O4 NPs were stable under the reaction conditions and reused for up to eight cycles without appreciable loss in the yield of benzoic acid. According to mechanistic insight, the KOH acts as a second oxygen source and is essential for the synthesis of carboxylic acid from alcohols. The hydrogen gas was found to be the only byproduct of this method detected by chemical reactions.
Keywords: nano-NiCo2O4; dehydrogenative oxidation; direct oxidation of primary alcohols; carboxylic acids; green synthesis; recyclability